Contribution to the functional analysis of genes involved in cyclic GMP signaling in bacteria of the Burkholderia cepacia complex - Alves, Sofia Patrão Neves, 1989- (2013)
Tese de mestrado. Biologia (Biologia Humana e Ambiente). Universidade de Lisboa, Faculdade de Ciências, 2013